Determination of embryotoxic dose limit of detomidine with in-ovo model - Rahmi Canbar; Muhittin Uslu; Öznur Tufan; Enver Yazar (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study is to determine the embryotoxic dose limit of detomidine with an in-ovo model using fertile hen?s eggs. Materials and Methods: 210 fertile eggs were divided into 7 equal (n: 30) groups and placed in the incubator under optimum conditions. No application was made to the first group. On the seventh day, normal saline solution, 10, 5, 2.5, 1.25, and 0.625 mg/kg doses of detomidine were administered to egg air-sacs in the other groups, respectively. On the 21st day, the eggs were opened and malformations, dead embryos and non-fertile eggs were determined. Results: While 3, 2, 4, 6 and 5 dead embryos were determined in 0.625, 1.25, 2.5, 5, and 10 mg/kg treated groups, respectively, no dead embryos were observed in the control and saline groups. While one non-fertile egg was determined in the control and 5 mg/kg detomidine groups, no nonfertile eggs were observed in the other groups. Mortality rates of detomidine group at doses of 2.5, 5 and 10 mg/kg were higher than the control and saline groups (p<0.05). Conclusion: Considering that the used smallest dose is 7.8 times higher than the highest recommended dose for the target species, recommended dose can be accepted safe in pregnant mammals for embryonic death. However, considering that the dose should be 100 times lower as a safety factor for mammals, it should be taken into account that negativities may also be observed.